1990
DOI: 10.1021/ic00337a007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus ylides as hard donor ligands: synthesis and characterization of MCl4(ylide-O)(THF) (M = Ti, Zr, Hf; ylide = (acetylmethylene)triphenylphosphorane, (benzoylmethylene)triphenylphosphorane). Molecular structure of trans-((acetylmethylene)triphenylphosphorane-O)(tetrahydrofuran)tetrachlorotitanium-(IV)-tetrahydrofuran

Abstract: 262ChemInform Abstract The title compounds (IV) are obtained as shown and characterized by NMR and IR spectroscopy. Their structure is confirmed by X-ray analysis of the Ti title complex (IVa) (M: Ti; space group P21/n, Z=4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 4 publications
(5 reference statements)
3
46
0
Order By: Relevance
“…5 A decreasing carbonyl streching frequency in the IR spectrum of the complex, resulting from major contributions from the resonance structure Ph 3 P -CH=C(Ph)-O À , confirms that the ligand is bound through the carbonyl oxygen ( Table 2).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…5 A decreasing carbonyl streching frequency in the IR spectrum of the complex, resulting from major contributions from the resonance structure Ph 3 P -CH=C(Ph)-O À , confirms that the ligand is bound through the carbonyl oxygen ( Table 2).…”
Section: Resultsmentioning
confidence: 68%
“…This is in accordance with the general trend of the coupling constants: free ylide b O-coordinated ylide b ylide hydrohalide salt (phosphonium salt) b C-coordinated ylide. 5 We often found that the complexes of the ylides generated with early transition metals are very unstable and not isolable. These intermediates undergo consecutive reactions in which one NMe 2 group is transferred from the starting metal complex to the ylide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] They are versatile ligands for catalysts in a very small number of catalytic reactions such as, for example, the hydrogenation of olefins 20 and the cyclotrimerization 21 and polymerization of acetylenes, 22 but the most important application is in the industrially used SHOP process. 23 The α-keto-stabilized phosphorus ylides are distinguishable from no stabilized ylides, since they can be easily handled due to an additional stabilization from delocalization of the negative charge.…”
Section: Introductionmentioning
confidence: 99%
“…In the compounds reported to date, the chemical behavior of the a-ketostabilized phosphorus ylides has been clearly dominated by the C-coordinated form [7][8][9][10][11], and very few examples of O-coordinated ylides are known [6,[12][13][14][15]. Some of these examples contain the ylide O-coordinated to a hard, very exophilic metal center, as Sn(IV) [12] or group 4 metals in high oxidation number [13].…”
Section: Introductionmentioning
confidence: 99%